2012
DOI: 10.1182/blood-2011-12-398834
|View full text |Cite
|
Sign up to set email alerts
|

Mcl-1 and Bcl-xL coordinately regulate megakaryocyte survival

Abstract: Mature megakaryocytes depend on the function of Bcl-x L , a member of the Bcl-2 family of prosurvival proteins, to proceed safely through the process of platelet shedding. Despite this, loss of Bcl-x L does not prevent the growth and maturation of megakaryocytes, suggesting redundancy with other prosurvival proteins. We therefore generated mice with a megakaryocyte-specific deletion of Mcl-1, which is known to be expressed in megakaryocytes. Megakaryopoiesis, platelet production, and platelet lifespan were unp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 40 publications
5
63
0
Order By: Relevance
“…These results indicated that, among the five members of the anti-apoptotic Bcl-2 family, either existence of Mcl-1 or Bcl-xL is required for the development and survival of megakaryocytes in both developing and adult mice. During revision of this manuscript, Debrincat et al 33 published a paper on line reporting the importance of these anti-apoptotic proteins in megakaryocyte survival, which agree with our current findings. Our present study now provides solid evidence that Mcl-1 and Bcl-xL have an important pro-survival role in preventing Bak/Bax-dependent megakaryocyte apoptosis in both developing and adult mice.…”
Section: Discussionsupporting
confidence: 90%
“…These results indicated that, among the five members of the anti-apoptotic Bcl-2 family, either existence of Mcl-1 or Bcl-xL is required for the development and survival of megakaryocytes in both developing and adult mice. During revision of this manuscript, Debrincat et al 33 published a paper on line reporting the importance of these anti-apoptotic proteins in megakaryocyte survival, which agree with our current findings. Our present study now provides solid evidence that Mcl-1 and Bcl-xL have an important pro-survival role in preventing Bak/Bax-dependent megakaryocyte apoptosis in both developing and adult mice.…”
Section: Discussionsupporting
confidence: 90%
“…However, staurosporine does not stimulate thrombopoiesis, rather, it causes mitochondrial damage, failure of proplatelet formation and death. Taken together, our results and those of several recent studies 18,22,[28][29][30]56,57 leave little room for the notion that apoptosis, as it is currently defined 54 , is required for, or can augment, platelet production by megakaryocytes. It remains possible that one or more components of the apoptotic machinery may play a role in the process, but convincing evidence for this has yet to emerge.…”
Section: Discussionsupporting
confidence: 59%
“…In megakaryocytes, MCL-1 and BCL-X L are both required to keep BAK and BAX in check 18,28,29 . Their simultaneous deletion leads to a failure of megakaryopoiesis, haemorrhage and embryonic lethality.…”
mentioning
confidence: 99%
“…CLEC-2 (CLEC1B -Mouse Genome Informatics), a C-type (9) lectin receptor on platelets that binds to podoplanin on LECs, is important for platelet aggregation at the junctions between developing lymph sacs and the CVs (Bertozzi et al, 2010;SuzukiInoue et al, 2010;Osada et al, 2012). Mice deficient in megakaryocytes, platelets or platelet aggregation, or with mutations disrupting podoplanin, O-glycosylation (a key post-translational modification of podoplanin), CLEC-2, or SLP-76 (LCP2-Mouse Genome Informatics) signalling in platelets, all exhibit blood-filled lymphatic vessels (Fu et al, 2008;Uhrin et al, 2010;Carromolino et al, 2010;Bertozzi et al, 2010;Suzuki-Inoue et al, 2010;Debrincat et al, 2012;Osada et al, 2012), reflecting the aberrant maintenance of blood-lymphatic vascular connections. Whether separation of the two vascular compartments is mediated solely by platelets acting as a physical barrier to 'plug' openings between veins and lymph sacs/lymphatic vessels, or whether platelet-LEC interaction results in downstream signalling events important for blood-lymphatic vascular separation remains to be established.…”
Section: Haematopoietic Cellsmentioning
confidence: 99%